Lignocellulosic thermoplastic composite from shredded waste paper / Bashirah Mohd Surur - Mohd Surur, Bashirah (1999)
Shredded waste paper is one of the abundant sources of used fiber. It has the potential to be use as reinforcing fillers in thermoplastic composite. In this experiment the waste paper thermoplastic composite was made through melt-blending process and its physical and mechanica/ properties were determined. The waste paper and polypropylene (PP) were blended in a dispersion mixer machine and then made into a composite using a mould, with waste paper percentage varying from 0 to 30%. The maleic anhydride grafted polypropylene (MAPP) was added to improve the bonding and interaction between the hydrophilic waste paper and hydrophobic polymer matrix. Composites produced were tested for tensile, flexural and water absorption properties. Results were compared to composite made from 100% neat PP. For thermoplastic composite without MAPP, loading of waste paper into the composite decrease the tensile strength and its ability to elongate. The higher amount of waste paper however increase the modulus of elasticity, water absorption and the flexural strength. The addition of MAPP in thermoplastic composite helps to improved the properties of composite. The flexural and tensile strength increases with the addition of MAPP. Overall, the waste paper was found to be a suitable material to be use in the manufacture of thermoplastic composite.